Lifestyle behavior of physiotherapy students from Ecuador upon admission to higher education: a cross-sectional study - Gutiérrez-Espinoza, Héctor; Cassola-Cajiao, María; Garzón-Ulloa, Emilia; Celi-Lalama, Daniela; Bastidas-Caldes, Carlos; Araya-Quintanilla, Felipe; Cristi-Montero, Carlos; López-Gil, José Francisco (Frontiers in Sports and Active Living, 2024)
Introduction Admission to university has been identified as a period involving the adoption of unhealthy lifestyle behaviors. However, few studies have addressed the extent of this experience among Latin American university students. The aim of this study was twofold: first, to describe anthropometric variables, body composition, physical activity, sedentary behavior, sleep duration and quality, diet, and alcohol consumption in first-year students entering physiotherapy school at the Universidad de las Americas in Quito, Ecuador; second, to test differences in these variables between sexes. Methods A total of 116 students were recruited. Sociodemographic variables, anthropometric indices, body composition, physical activity, sedentary behavior, sleep quality and duration, adherence to 24-hour movement guidelines, physical fitness (i.e., handgrip strength), diet, alcohol consumption, and smoking habits were evaluated. Results A total of 50 male (43.1%) and 66 female (56.9%) students were assessed. Overall, the adherence to the 24-hour movement guidelines of the students upon admission to university was 8.6%. Conversely, 86 students (74.1%) did not meet any of the recommendations. Upon admission to university, only 8.6% of the students (female 2.6%; male 6%) met the overall 24-hour movement guidelines. Additionally, 82 students (70.7%) needed changes in diet quality, 81 students (69.8%) had significant sleep disturbances, and 22 students (18.9%) had harmful alcohol consumption. A greater proportion of males met all three 24-h movement recommendations (p = 0.025) than females did. In addition, females reported a greater percentage of occasional smokers (p = 0.025) and a greater prevalence of obesity (p < 0.001), a lower level of physical activity (p < 0.001), and a greater percentage of sleep disturbance (p < 0.001). Conversely, males reported greater waist circumference (p = 0.005), weight (p < 0.001), handgrip strength (p < 0.001), and a greater percentage of harmful alcohol consumption (p < 0.001). Discussion Our study showed that upon admission to university, overall adherence to the 24-hour movement guidelines is low among university students. Additionally, a high percentage of students reported unhealthy lifestyle behaviors, with differences according to sex. Our findings could lead to the use of specific sex-specific strategies for the prevention and promotion of movement and lifestyle behaviors during this critical period.